Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-77100-3
|View full text |Cite
|
Sign up to set email alerts
|

Differently expressed microRNA in response to the first Ig replacement therapy in common variable immunodeficiency patients

Abstract: Common variable immunodeficiency (CVID) is a complex primary immunodeficiency disorder characterized by a high clinical and genetic heterogeneity. The molecular underlying causes of CVID are not still now clear and the delays in diagnosis and treatment worsen the prognosis of the patients. MicroRNAs are non-coding, endogenous small RNAs often deregulated in human diseases, such as autoimmune and other immune-based disorders. In the present study, we aimed to evaluate miRNAs associated with the CVID and, in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Regarding miRNAs, the seven miRNAs identi ed in our study have been widely reported in various diseases [28][29][30][31][32]. For example, hsa-miR-1825 was found to be down-regulated in patients with common variable immunode ciency (CVID) who received Ig infusion [33],…”
Section: Discussionmentioning
confidence: 84%
“…Regarding miRNAs, the seven miRNAs identi ed in our study have been widely reported in various diseases [28][29][30][31][32]. For example, hsa-miR-1825 was found to be down-regulated in patients with common variable immunode ciency (CVID) who received Ig infusion [33],…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, IVIg is thought to interfere 7 Oxidative Medicine and Cellular Longevity with the passage of autoimmune cells across the bloodnerve barrier and to reduce antibody production by B cells, interfere with B cell proliferation through cell surface receptors, block the activity of certain B cell subtypes, interrupt several steps in the complement activation cascade, and affect activity mediated by the Fc receptor [31,34]. The correlations between IVIg treatment effectiveness and miRNA level were described in many studies in different clinical situations [35][36][37][38]. IVIg replacement therapy in different immunodeficiency patients is thought to be able to modulate miRNA level.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, miR-1972 has been identified to regulate various targets, including EDN1, CD274, and PDCD1LG2 [ 33 ]. These targets play pivotal roles in processes such as respiratory burst and T-cell activation, highlighting miR-1972’s association with T and B cell signaling as well as TNFR1 signaling pathways [ 34 ]. Notably, in the context of chronic myeloid leukemia, overexpression of miR-1972 has been linked to cell cycle arrest at the G2-M phase [ 35 ].…”
Section: Discussionmentioning
confidence: 99%